ANALISIS MOTIVASI INTRINSIK BELAJAR SISWA KELAS V SEKOLAH DASAR SE-GUGUS 1 KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - Reksi Septio Asmar; Otang Kurniaman; Neni Hermita (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
ABSTRACTThis background of research is students who experience barriers to learning This study aims to determine the factors that influence students intrinsic learning motivation and the factors that most influence student motivation to learn. This research was conducted in class V Elementary School in Cluster 1 Payung Sekaki district Pekanbaru city. Based  on the results of the study, it was found that the factors that influence students intrinsic motivation consist of ideals, student ability, student condition factor and dynamic elements. On ideals factors include active learning to achieve goals, the desire to succeed in learning and need for learning. In the factors of students abilities, including working alone, it is difficult to understand the material presented and dare to express opinions. On the factors of student conditions include enthusiasm in learning, discipline in learning, physical of students and spiritual condition of students. On Dynamic elements include high willingness, attention of learning, positive views in learning and students feelings toward learning. So, the factors that influence the intrinsic motivation of learn class V of Primary School Se-Gugus 1 of Payung Sekaki district , Pekanbaru city are the ideals which affect  7,565%.